2010
DOI: 10.1002/bit.23014
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid pretreatment of cellulosic biomass: Enzymatic hydrolysis and ionic liquid recycle

Abstract: Ionic liquids (ILs) are promising solvents for the pretreatment of biomass as certain ILs are able to completely solubilize lignocellulose. The cellulose can readily be precipitated with an anti-solvent for further hydrolysis to glucose, but the anti-solvent must be removed for the IL to be recovered and recycled. We describe the use of aqueous kosmotropic salt solutions to form a three-phase system that precipitates the biomass, forming IL-rich and salt-rich phases. The phase behavior of [Emim][Ac] and aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
205
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(209 citation statements)
references
References 33 publications
2
205
0
2
Order By: Relevance
“…S10), its activity was measured in the presence of the ionic liquids 1, 3-dimethylimidazolium dimethyl phosphate (DMIM)DMP) and 1-ethyl-3-methylimidazole acetate ((EMIM)OAc), which could potentially be used to pretreat substrates like Miscanthus 17 . The concentrations tested, 25 and 50% (v/v), are well above the expected residual ionic liquid of 10-15% that may be carried over after pretreatment 18 .…”
Section: Enrichment and Extraction Of Native Proteinmentioning
confidence: 99%
“…S10), its activity was measured in the presence of the ionic liquids 1, 3-dimethylimidazolium dimethyl phosphate (DMIM)DMP) and 1-ethyl-3-methylimidazole acetate ((EMIM)OAc), which could potentially be used to pretreat substrates like Miscanthus 17 . The concentrations tested, 25 and 50% (v/v), are well above the expected residual ionic liquid of 10-15% that may be carried over after pretreatment 18 .…”
Section: Enrichment and Extraction Of Native Proteinmentioning
confidence: 99%
“…Liu et al (2012) reported that lignin showed better solubility results than cellulose in amino-acid based IL. In another study, Shill et al (2011) indicated that the p-p interactions of the IL cation with lignin assisted in lignin solubilization. However, complete delignification of biomass is difficult due to the location of lignin within the lignin-carbohydrate complex, strong poly-ring bonds of C-O-C, C-C, and hydrophobicity (Kim et al 2003).…”
Section: Quantification Of Lignin Contentmentioning
confidence: 99%
“…For chloride-based ILs, the presence of water should coordinate with chloride ions (Shill et al 2011) (Fig. 2).…”
Section: An Insight Into Il Pretreatment Of Corn Stalkmentioning
confidence: 99%